2022
DOI: 10.1002/smll.202201487
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of High‐Content Actives Using Biodegradable Silk Materials

Abstract: There is a compelling need across several industries to substitute non‐degradable, intentionally added microplastics with biodegradable alternatives. Nonetheless, stringent performance criteria in actives’ controlled release and manufacturing at scale of emerging materials hinder the replacement of polymers used for microplastics fabrication with circular ones. Here, the authors demonstrate that active microencapsulation in a structural protein such as silk fibroin can be achieved by modulating protein protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Previous studies have also shown that a positive charge can promote uptake of “hard” nanoparticles such as carbon dots and nanoceria by leaf mesophyll cells and chloroplasts of cotton and maize plants after foliar topical delivery . The current results also suggest that the charge of “soft” materials such as these polymer nanocarriers, or biopolymers that have been proposed as nanocarriers, , may behave similarly to the charge from “hard” particles with respect to nanomaterial-mesophyll cell interactions despite differences in their stiffness. However, the influence of other properties such as the flexibility of polymer nanomaterials may affect their ability to penetrate through plant barriers such as the cell wall and cell membrane.…”
Section: Resultssupporting
confidence: 68%
“…Previous studies have also shown that a positive charge can promote uptake of “hard” nanoparticles such as carbon dots and nanoceria by leaf mesophyll cells and chloroplasts of cotton and maize plants after foliar topical delivery . The current results also suggest that the charge of “soft” materials such as these polymer nanocarriers, or biopolymers that have been proposed as nanocarriers, , may behave similarly to the charge from “hard” particles with respect to nanomaterial-mesophyll cell interactions despite differences in their stiffness. However, the influence of other properties such as the flexibility of polymer nanomaterials may affect their ability to penetrate through plant barriers such as the cell wall and cell membrane.…”
Section: Resultssupporting
confidence: 68%
“…1A and fig. S1A) ( 29 ), followed by water annealing of those particles to induce formation of ordered molecular structures and render them water insoluble ( 30 ). The choice of the spray drying technique was based on its high efficiency in producing grams of protein powders per hour and its wide use in the industry ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Future work may extend to the encapsulation of micro-and nanomaterials into microneedles both in the form of payloads or carriers for other actives, such as metal nanoparticles for micronutrients and mesoporous silicon nanoparticles, for controlled release, where on-site in vitro aggregation and thus dysfunction of nanomaterials may be prevented. [3,34] The properties of microneedles can also be tuned to decrease burst release and target a sustained release of payloads via alternative biomaterials and post-treatment. [35]…”
Section: Microneedle Utility In Cereal Cropsmentioning
confidence: 99%